The antecedents of food waste recycling behaviour among households in Kuala Terengganu / Noorazlin Ramli … [et al.] - Ramli, Noorazlin; Shahril, Nurul Syuhadah; Md Daud, Nur Afifah; Abd Ghani, Fatimah; Mohd Abd Majid, Hayati Adilin (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This study aims to identify the relationship between the anticipated negative emotions of guilt, awareness of consequences, and habits toward recycling food waste among households in Kuala Terengganu. The importance of each proposed variable is revealed by the analysis of a total of 177 valid respondents using the 27th version of the Statistical Package for the Social Sciences (SPSS). Using a questionnaire created in Google Forms and a direct response system, the data were gathered in Kuala Terengganu among local respondents ranging in age from 18 to 64. Convenience sampling was the method employed in this study to select the respondents. The results revealed that only one independent variable, the anticipated negative emotion of guilt, significantly impacts households' food waste recycling behavior. The findings will be useful to households, governments, and researchers looking for a solution to the problem of food waste.